THE MEDIATING ROLE OF INNOVATION ON THE RELATIONSHIP BETWEEN SUPPLY CHAIN MANAGEMENT AND COMPANY PERFORMANCE IN THE KINGDOM OF BAHRAIN - Alabdullah, Tariq Tawfeeq Yousif; Kanaan-Jebna, Abdulkarim (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2023)
This research focuses on critical independent variables, including information quantity and quality sharing, and the adoption of lean practices within companies. It examines these variables to understand their effects on corporate performance using innovation as a mediator. Data from registered non-financial businesses in Bahrain are utilized, and Smart PLS is recommended for analysis. The study aims to unravel the intricate relationships among these variables in Bahrain's nonfinancial sector. Conceptually, it contributes to a deeper understanding of the interplay between information sharing, lean methods, innovation, and firm performance, with a focus on the mediating role of innovation. Practically, it offers insights for business leaders, policymakers, and professionals, enhancing awareness of information sharing, quality, and lean methods, thereby enabling informed decisions to improve corporate performance and foster innovation-driven growth. The uniqueness of this research lies in its holistic approach, examining the interconnectedness of information sharing, lean practices, innovation, and firm performance. Unlike previous studies that explored these aspects in isolation, this research integrates them into a comprehensive framework, enhancing its value to the field and potential impact on business operations. It serves as a valuable resource for academics, researchers, corporate executives, employees, and regulators. Academics and researchers benefit from its conceptual and empirical contributions, while corporate stakeholders gain practical insights for enhancing performance and promoting innovation. Regulators can leverage the findings to develop legislative structures that facilitate information sharing, quality, and lean practices in Bahrain's nonfinancial sector.